EKSPLORASI MOTIF BATIK CUPAT MANGGU PADA PERNCANGAN INTERIOR RESTORAN HOTEL SWISS-BELRESORT DAGO HERITAGE BANDUNG - Adinda Zhafira Hanun; Detty Fitriany (Universitas Mercu Buana, 2023)
The implementation of interior concept that contain elements of local culture based on the area where a hotel is located is a form of respect for the culture itself that can be carried out by an interior designer in designing the hotel. Swiss-Belresort Dago Heritage Bandung is one of the four-star resort hotels that applies this concept, as a tribute to the local culture of West Java, according to the context and location where the hotel was built. One of the local elements representing the culture of the West Java region that can be raised is the decorative elements on batik, especially particular batik of the West Java region because Swiss-Belresort Dago Heritage Bandung is located in West Java. Cupat Manggu is a typical West Javanese batik motif that describes the philosophy of an agrarian concept in West Java with a flora theme. The Cupat Manggu (mangosteen fruit) motif is a typical Tasikmalaya motif inspired by fruit (mangosteen) motif which can be explored further as an aesthetic element in the interior design. This research explains the exploration of the Cupat Manggu batik motif in the interior of the Swiss-Belresort Dago Heritage Bandung hotel restaurant. The design method is divided into five stages, namely the identification & empatize, define, ideate, prototype, and design result stages. The result of this design is the visualization of the new Swiss-Belresort Dago Heritage Bandung hotel restaurant space with the implementation of the Cupat Manggu batik motif which is made with stylized shapes and more modern interior finishing materials.